2015
DOI: 10.1002/psc.2776
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of chemically synthesized mussel adhesive peptide sequences containing DOPA on stainless steel

Abstract: The adsorption of proteins at solid-liquid interfaces is important in biosensor and biomaterial applications. Marine mussels affix themselves to surfaces using a highly cross-linked, protein-based adhesive containing a high proportion of L-3,4-dihydroxyphenylalanine (DOPA) residues. In this work, the effect of DOPA residues on protein adhesion on stainless steel surfaces was studied using a quartz crystal microbalance with dissipation system. The adsorption of two repetitive peptide motifs, KGYKYYGGSS and KGYK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…As a result, nitinol stents, which are frequently used due to their unique mechanical properties and excellent biocompatibility, in fact display a TiO 2 surface that enables an easy functionalization with DOPA-containing peptides by dip coating. This mechanism is transferable to stainless steel, which was likewise coatable with the mussel-derived peptide and provides an alternative to nitinol when higher mechanical stability is desired. Herein, a coordination bond between the catechol and the respective metal oxide is formed .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, nitinol stents, which are frequently used due to their unique mechanical properties and excellent biocompatibility, in fact display a TiO 2 surface that enables an easy functionalization with DOPA-containing peptides by dip coating. This mechanism is transferable to stainless steel, which was likewise coatable with the mussel-derived peptide and provides an alternative to nitinol when higher mechanical stability is desired. Herein, a coordination bond between the catechol and the respective metal oxide is formed .…”
Section: Discussionmentioning
confidence: 99%
“…The adhesion proteins secreted by marine mussels bind strongly to virtually all inorganic and organic surfaces in aqueous environments, accordingly serving as an intractable problem in the field of marine antifouling. , A common feature of such proteins is that they contain a high content of 3,4-dihydroxy- l -phenylalanine ( l -DOPA), which is considered to be responsible for their capacity to compete successfully with water at the surface and cross-link under water. , In the most recent decade, interaction mechanisms of DOPA side chains embedded in proteins and solid surfaces have been extensively studied, owing to a growing attraction in the respects of antifouling strategies and biomimetic adhesion. It can be concluded that DOPA plays an important part in the interactions through H-bonding, , coordination with metal/metal oxide, , or covalent cross-linking, , of which the detailed binding mechanisms of DOPA to different surfaces is an extremely important research topic, attracting great interests of scientists.…”
Section: Introductionmentioning
confidence: 99%
“…1316 Many research studies are focused on revealing and mimicking the adhesive materials. The mimicking mussel is widely used in medicine, food, metallurgy, and other fields, 1719 whose application in the surface modification of the flame retardant has not been reported. Tannic acid is a complex polyhydric phenol, in which there are multiple phenolic hydroxyl groups, which can be a carbonization agent in IFR and simultaneously form a stable chelate with Fe 3+ .…”
Section: Introductionmentioning
confidence: 99%
“…Mussels are common creatures living in the ocean, which can secrete strong adhesion protein, clinging to the surface of many substances such as bone grafts, plants, glass products, metal components, polymer materials, minerals, and so forth. Many research studies are focused on revealing and mimicking the adhesive materials. The mimicking mussel is widely used in medicine, food, metallurgy, and other fields, whose application in the surface modification of the flame retardant has not been reported. Tannic acid is a complex polyhydric phenol, in which there are multiple phenolic hydroxyl groups, which can be a carbonization agent in IFR and simultaneously form a stable chelate with Fe 3+ .…”
Section: Introductionmentioning
confidence: 99%